Neurointerventions and crime prevention. An ethically inappropriate discussion? - Ryberg, Jesper (Teoria e Critica della Regolazione Sociale / Theory and Criticism of Social Regulation, 2021)
An increasing number of philosophers and other theorists have in recent years become preoccupied with the question as to whether it is ethically acceptable to use neurointerventions – that is, interventions which in one way or another operate directly on the brain of a subject – as an instrument in crime prevention. But have the theorists who engage in this discussion been led astray? Should such a discussion in itself be regarded ethically inappropriate? This article considers three objections to the current neuroethical discussion of crime prevention: 1) That the discussion is too hypothetical; 2) that it derails the traditional discussion of crime prevention by fundamentally misdiagnosing the problem of crime; 3) that the discussion may have undesirable implications by being misunderstood or even misused in political contexts. It is argued that, even though theorists do possess a responsibility for the implications of the research they engage in, the three objections should all be dismissed